The haves and the have-nots a brief and idiosyncratic history of global inequality - Milanovic, Branko (New York, NY Basic Books, 2011)
One of the world's leading experts on wealth, poverty, and the gap that separates them, explains how wealth is unevenly spread throughout our world, now and through time. Economist Branko Milanovic uses history, literature and stories straight out of today's newspapers, to discuss one of the major divisions in our social lives: between the haves and the have-nots. He reveals just how rich Elizabeth Bennet's suitor Mr. Darcy really was; how much Anna Karenina gained by falling in love; how wealthy ancient Romans compare to today's super-rich; where in Kenyan income distribution was Obama's grandfather; how we should think about Marxism in a modern world; and how location where one is born determines his wealth. He goes beyond mere entertainment to explain why inequality matters, how it damages our economic prospects, and how it can threaten the foundations of the social order that we take for granted.--From publisher description.
Unequal people : inequality among individuals within a nation. Romance and riches ; Anna Vronskaya? ; Who was the richest person ever? ; How unequal was the Roman Empire? ; Was socialism egalitarian? ; In what Parisian arrondissement should you live in the thirteenth century and today? ; Who gains from fiscal redistribution? ; Can several countries exist in one? Will China survive in 2048? ; Two students of inequality : Vilfredo Pareto and Simon Kuznets -- Unequal nations : inequality among countries in the world. Why was Marx led astray? ; How unequal is today's world? ; How much of your income is determined at birth? ; Should the whole world be composed of gated communities? ; Who are the Harraga? ; The three generations of Obamas ; Did the world become more unequal during deglobalization? -- Unequal world : inequality among citizens in the world. Where in the global income distribution are you? ; Does the world have a middle class? ; How different are the United States and the European Union? ; Why are Asia and Latin America mirror images of each other? ; Do you want to know the winner before the game begins? ; Income inequality and the Global Financial Crisis ; Did colonizers exploit as much as they could? ; Why was Rawls indifferent to global inequality? ; Geopolitics in light of (or enlightened by) economics.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Income distribution -- History; Wealth -- History; Poverty -- History